O BRASIL MULTIFACETADO: GÊNERO, DEMOCRACIA E DESIGUALDADES NO SÉCULO XXI (Interdisciplinary Studies Journal, 2024)
The present work consists of a critical review of the book “Gender and inequalities: limits of democracy in Brazil”, by Flávia Biroli. Published in 2018, the work is a relevant contribution in the field of political theory, feminism and studies on democracy, bringing important reflections to think about Brazil today. Among the issues raised by the book, and developed in this exhibition, are the consequences of neoconservatism and neoliberalism for democracy, such as the growing depoliticizationof society, alongside disproportionate reactions to issues such as gender, class, race and gender equality. ethnicity in states that claim to be democratic. Such a picture signals  setbacks in terms of fundamental rights, directly impacting women's lives and the exercise of their citizenship.